2018
DOI: 10.1002/ajmg.b.32628
|View full text |Cite
|
Sign up to set email alerts
|

Rubinstein–Taybi syndrome: New neuroradiological and neuropsychiatric insights from a multidisciplinary approach

Abstract: Rubinstein-Taybi syndrome is a rare, autosomal dominant, plurimalformative disorder that is clinically characterized by intellectual disability and a wide spectrum of congenital anomalies; facial dysmorphisms are typical, and broad thumbs and great toes are particularly distinctive. Its genetic basis is only partially known, with a detection rate of approximately 65-70%; specifically, microdeletions or mutations in the CREBBP or EP300 genes can be found. Much is known about its clinical features and health-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…Furthermore, protein–protein interaction networks (https://string-db.org/) show known and predicted interactions with other proteins having a role in histone‐mediated chromatin remodeling. CREBBP, an interactor of the KMT2A transactivator domain, supports the role of some of these proteins in CVJ anomalies: de novo LoF/deletion variants in the CREBBP gene are responsible for Rubinstein‐Taybi syndrome 1 (RSTS1, OMIM # 180849), a severe multisystemic disorder in which Chiari malformation type I is common (Ajmone et al, 2018; Lee et al, 2015) and a high risk of cervical vertebral anomalies has been reported, including vertebral fusion and abnormalities of the odontoid process (Milani et al, 2015; Yamamoto et al, 2005). Similar findings in a few cases of Kabuki syndrome (OMIM # 147920 and # 300867; Ciprero et al, 2005)—and in particular in one case associated with a LoF variant of KDM6A (Cheon & Ko, 2015)—further point to alterations in histone acetylation and methylation as causative of Chiari type I.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, protein–protein interaction networks (https://string-db.org/) show known and predicted interactions with other proteins having a role in histone‐mediated chromatin remodeling. CREBBP, an interactor of the KMT2A transactivator domain, supports the role of some of these proteins in CVJ anomalies: de novo LoF/deletion variants in the CREBBP gene are responsible for Rubinstein‐Taybi syndrome 1 (RSTS1, OMIM # 180849), a severe multisystemic disorder in which Chiari malformation type I is common (Ajmone et al, 2018; Lee et al, 2015) and a high risk of cervical vertebral anomalies has been reported, including vertebral fusion and abnormalities of the odontoid process (Milani et al, 2015; Yamamoto et al, 2005). Similar findings in a few cases of Kabuki syndrome (OMIM # 147920 and # 300867; Ciprero et al, 2005)—and in particular in one case associated with a LoF variant of KDM6A (Cheon & Ko, 2015)—further point to alterations in histone acetylation and methylation as causative of Chiari type I.…”
Section: Discussionmentioning
confidence: 95%
“…CREBBP, an interactor of the KMT2A transactivator domain, supports the role of some of these proteins in CVJ anomalies: de novo LoF/deletion variants in the CREBBP gene are responsible for Rubinstein-Taybi syndrome 1 (RSTS1, OMIM # 180849), a severe multisystemic disorder in which Chiari malformation type I is common (Ajmone et al, 2018;Lee et al, 2015) and a high risk of cervical vertebral anomalies has been reported, including vertebral fusion and abnormalities of the odontoid process (Milani et al, 2015;Yamamoto et al, 2005). Similar findings in a few cases of Kabuki syndrome (OMIM # 147920 and # 300867;Ciprero et al, 2005) other cervical defects (e.g., vertebral fusion), they may lead to severe neurological deterioration (Connor et al, 2001).…”
Section: Cvj Anomalies Of the 11 Participantsmentioning
confidence: 92%
“…Therefore, when genetic disorders disrupt epigenetic machinery molecules, brain malformations are a near-constant. This seems especially true for median structures of the brain, such as the corpus callosum and the cerebellar vermis as reported by different studies (Schaefer et al, 1997;Schrier et al, 2012;Willemsen et al, 2012;Maya et al, 2014;Ajmone et al, 2018). As more and more studies on the neurological aspects of the MDEM emerge, reports on other brain malformations are revealed.…”
Section: Discussionmentioning
confidence: 85%
“…As more and more studies on the neurological aspects of the MDEM emerge, reports on other brain malformations are revealed. Searching the literature for OB hypoplasia/aplasia in these conditions unveiled a large number of studies involving CHARGE syndrome (Lin et al, 1990;Harvey et al, 1991;Pinto et al, 2005), but only a couple of human reports on RSTS and KLFS (Ajmone et al, 2018;Ciaccio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, Ajmone et al described neuroradiological insights in 23 RSTS Italian patients and reported minor dysmorphic aspects of the cerebellar vermis in 58% and olfactory bulbs hypoplasia or aplasia in 32% of cases as was observed by us in case 2. 16 Moreover, abnormalities of the gallbladder were present in 22% of cases and were detected by ultrasonography. This feature has, to the best of our knowledge, not been described before in RSTS children and may therefore represent a prenatal hallmark of the syndrome.…”
Section: Phenotypementioning
confidence: 99%